Pengaruh Pola Asuh Orang Tua dan Disiplin Belajar Terhadap Hasil Belajar Matematika Peserta Didik - Risdayanti, Suci; Abrar, Andi Ika Prasasti (Alauddin Journal of Mathematics Education, 2022)
The objectives of this study are: (1) to determine the influence of parental parenting patterns on the mathematics learning outcomes of class X SMA Negeri 5 Bulukumba students, (2) to determine the influence of learning discipline on the mathematics learning outcomes of class X SMA Negeri 5 Bulukumba students, and (3) to determine the influence of parental parenting and mathematics learning outcomes simultaneously on the mathematics learning outcomes of class X SMA Negeri 5 Bulukumba students. The type of research used is causal comparative research or what is often called ex post facto research. This research was carried out at SMA Negeri 5 Bulukumba with a research sample, namely class X students of SMA Negeri 5 Bulukumba which totaled 105 people. The research instruments used include a questionnaire on parenting and a questionnaire on learning discipline. Data analysis in this study used descriptive statistics and inferential statistics in the form of simple and multiple linear regression analysis. Furthermore, based on the results of data analysis, it was obtained that: (1) democratic parenting affects the mathematics learning outcomes of students of class X SMA Negeri 5 Bulukumba, (2) learning discipline affects the mathematics learning outcomes of students of class X SMA Negeri 5 Bulukumba, and (3) democratic parenting and learning discipline simultaneously affects the mathematics learning outcomes of students of class X SMA Negeri 5 Bulukumba.